Competitive Play among a sample of Students in Basic Education Stage 2, First Cycle, in Damascus schools - omer dallal, dallal (Journal of Social Sciences and Humanities, 2024)
This research aims to identify the Level and motives for competitive playing among a sample of students in the basic education stage (2), in Damascus schools. Their number was (550) male and female students and two measures of competitive play and motivations for competitive play were used to answer the research questions. A set of results were reached, most notably: high level of competitive play, and that the most important motives for competitive play were (Personal Growth, Innovation, Performance Increase, Relational Damage, Unethical Behavior), in addition to the presence of statistically significant differences between the members of the study sample. Males and females on the scale of competitive play, and the difference was in favor of males. It was also shown that the motives for competitive play